1973
DOI: 10.1128/aac.3.4.451
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rifampin on the Immune Response in Guinea Pigs

Abstract: The effect of an oral dose of 20 mg of rifampin per kg per day on the immune response to killed Mycobacterium bovis var. BCG, 1-chloro-2,4-dinitrobenzene (DNCB), and sheep red blood cells (SRBC) was studied in adult female guinea pigs. Fully established cutaneous reactions to BCG or DNCB were markedly reduced during rifampin treatment but reverted to pretreatment levels after the drug was discontinued. When treatment was begun 7 days after immunization, positive reactions did not occur … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
0

Year Published

1974
1974
1984
1984

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 8 publications
2
14
0
Order By: Relevance
“…These results indicate that prolonged therapy with rifampin in humans exerts an immunosuppressive effect and are in accord with previously reported studies in animals (3,10,12 Although rifampin exerted a demonstrable immunosuppressive effect, all patients showed favorable responses to therapy. Acid-fast bacilli were eliminated from the sputum of all patients, and all are currently being treated as outpatients.…”
Section: Ruben Winkelstein and Fotiadissupporting
confidence: 81%
“…These results indicate that prolonged therapy with rifampin in humans exerts an immunosuppressive effect and are in accord with previously reported studies in animals (3,10,12 Although rifampin exerted a demonstrable immunosuppressive effect, all patients showed favorable responses to therapy. Acid-fast bacilli were eliminated from the sputum of all patients, and all are currently being treated as outpatients.…”
Section: Ruben Winkelstein and Fotiadissupporting
confidence: 81%
“…The dose of rifampin required to suppress the footpad reaction to PPD in this animal species was large when compared with the dose required to produce a similar effect in guinea pigs (2). In guinea pigs 20 mg of oral rifampin per kg partially suppressed the intradermal reaction to PPD in 14 days, but in mice 200 mg of parenteral rifampin per kg per day was required to produce significant suppression of that reaction ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…the antibody response to sheep erythrocytes (2). Thus, the antibiotic can inhibit both cell-mediated immunity (CMI) and antibody-mediated immunity.…”
mentioning
confidence: 99%
“…Antibacterial activity in cultures and the activities of the rifamycins inhibiting deoxyribonucleic acid-dependent ribonucleic acid polymerase appeared to correlate well. However, when these two types of activity, antiimmune and antibacterial, were compared, correlation was poor on occasion and indicated that the antiimmune activities and antibacterial activities of the rifamycins are probably not related.It has been reported previously (6) that some members of the ansamycin class of antibiotics, including certain rifamycins and streptovaricins, share the well-recognized immunosuppressive properties of rifampin (3,4,8,11). It was noted in that report that when the in vitro antibacterial activity of these substances was compared with their in vivo immunosuppressive activity, correlation was poor, suggesting that the two activities are unrelated.…”
mentioning
confidence: 78%
“…It has been reported previously (6) that some members of the ansamycin class of antibiotics, including certain rifamycins and streptovaricins, share the well-recognized immunosuppressive properties of rifampin (3,4,8,11). It was noted in that report that when the in vitro antibacterial activity of these substances was compared with their in vivo immunosuppressive activity, correlation was poor, suggesting that the two activities are unrelated.…”
mentioning
confidence: 83%